PENGEMBANGAN APLIKASI MEMANGGIL JASA KEBERSIHAN UNTUK MENDUKUNG LAPANGAN KERJA - Brydden Abelard; Pualam Dipa Nusantara (FAKULTAS TEKNIK, 2025)
In today's fast-paced and demanding life, time is very important. The need for cleaning services is becoming increasingly apparent. Balancing work, family and personal commitments often leaves limited time and energy for cleaning our environment. Apart from that, there are also freelance cleaning service workers who need a way to find customers. According to data from the Central Statistics Agency (BPS), freelance workers in Indonesia have reached 34 million people and some of them are freelance workers for cleaning. The aim of this research is to develop a web-based application that can help users find cleaning services and freelancers find customers. The web-based application development used in this research is the waterfall method with the steps: Requirements analysis, Planning, Design, Construct, Deployment and Maintenance. The programming languages used are: PhP, HTML, CSS, and Javascript. The results of this research have successfully developed a web-based application that can help users find cleaning services and freelancers to find customers. From the results of the evaluation of 50 respondents, 96% of them were satisfied.